Penguatan Kapasitas Sumber Daya Manusia UMKM di Pagedangan Tangerang dalam Meningkatkan Produktivitas Gerakan Pemuda Ansor - Dira Karlina; Windy Gustia Wardani; Ibrahim Ali Akbar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting local economic development and community welfare. However, many MSME actors still face challenges related to human resource capacity, productivity, business management, and adaptation to technological developments. Strengthening human resource competencies is essential to improve productivity and organizational performance, particularly among youth organizations involved in economic empowerment activities. Therefore, this Community Service Program (PKM) aimed to strengthen the human resource capacity of MSME actors in Pagedangan, Tangerang, in order to enhance the productivity of Gerakan Pemuda Ansor. The activity was conducted on May 19, 2026, at the Village Hall of Cicalengka, Pagedangan District, Tangerang Regency. The program was implemented by three lecturers from Universitas Pamulang and attended by 32 members of Gerakan Pemuda Ansor. The methods used included material presentations, practical exercises, discussions, and question-and-answer sessions. The implementation process consisted of three stages: preparation, implementation, and reporting. The results indicated an improvement in participants’ understanding of human resource development, productivity enhancement strategies, and effective organizational management. Participants demonstrated increased awareness of the importance of developing competencies, utilizing technology, and improving work efficiency to support MSME growth. The interactive activities also encouraged active participation and knowledge sharing among participants. Overall, the program contributed positively to strengthening human resource capacity and supporting the productivity improvement of Gerakan Pemuda Ansor members engaged in MSME activities.